Multiracial identity at work: Navigating career and professional dynamics postcollege. Issue 174 (5th November 2021) - Nayani, Farzana
Abstract: This article describes the challenges that multiracial students face in professional work while emphasizing potential resources and strategies for individuals who advise these students towards their career success.